MG-122 Atypical fish pattern consistent with insertion of 5' CBFB into 16p13 in a case of therapy-related acute myeloid leukaemia. (4th December 2015) - Raza, Adeel Mohammad; Sanchez, Jessica; Snower, Daniel; Adeyinka, Adewale
Abstract : Background: The inv (16) and related t (16;16) resulting in fusion of CBFB gene (16q22) to MYH11 (16p13) are not commonly observed in therapy-related AML (t-AML). Objective: To present a case of t-AML with CBFB/MYH11 fusion and rearrangement of chromosome 16 other than the commonly described inv (16) and related t (16;16). Case report: A 46-year-old woman presented with t-AML 1.25 years after adjuvant radiation and chemotherapy for rectal carcinoma. Peripheral blood showed marked reduction in neutrophils, 24% blasts and increased lymphocytes and monocytes. Bone marrow aspirates revealed large blasts with abundant cytoplasm, fine nuclear chromatin, occasional deep nuclear folds and prominent nucleoli. Bone core biopsy mainly consisted of blasts and was remarkable for numerous eosinophilic myelocytes and metamyelocytes. Cytogenetic analysis of bone marrow aspirate was interpreted as 46, XX, inv (16)(p13.3q22)[6]/47, idem, +8[14]/48, idem, +6, +8[2]. Interphase FISH analysis using the CBFB break-apart probe showed an atypical abnormal signal pattern of two CBFB fusion signals and one 5' CBFB probe signal. Metaphase FISH analysis showed an abnormal chromosome 16 with a CBFB fusion signal on one arm and a 5' CBFB signal on the other arm. The normal 16 homologue showed the expected one CBFB fusion signal. The CBFB/MYH11 fusion transcript type A was detected by RT-PCR. Conclusion: The abnormal CBFB pattern observed in this case differs from what is expected for an inv (16) or t (16:16), but can be explained by an insertion of 5' CBFB into 16p13. This case demonstrates that insertion of 5' CBFB into 16p13 is another mechanism of producing a CBFB /MYH11 fusion.